Single-pass tillage combined with herbicides and rice stubbles enhances weed control and yield of rapeseed in Bangladesh - Mohammad Hossain (Dysona. Applied Science, 2021)
South Asian farmers are turning to mechanized planting, crop stubble retention, and herbicide application to address the current labor shortage situation. The purpose of this on-farm study was to compare conventional plow tillage combined with manual weeding to single-pass tillage combined with herbicides on the overall weed control efficacy and seed yield ofrapeseed(Brassica napus L.) under northern Bangladesh conditions. During 2014–2016, the rapeseed variety ‘BARI Mustard-14’ was grown under two different tillage systems, plow tillage and single-pass tillage with zero-stubble and 50% standing stubbles of previously grown monsoon rice. The plow tillage was conducted using a two-wheel, while the single-pass tillage was performed using a versatile multi-crop planter. In plow tillage, weeds were managed by hand on three dates. In single-pass tillage, a pre-plant herbicide (glyphosate),  pre-emergence herbicide (pendimethalin), and post-emergence herbicide (isoproturon) were applied for weed control. Data revealed that the combination of single-pass tillage and herbicides with 50% rice stubbles resulted in the highest weed control efficacy. Additionally, this practice resulted in a 20% yield increase and a 70% increase in benefit-cost ratio compared with plow tillage and hand weedings combination without keeping any rice stubbles in the field.